Socially Assistive Robot HealthBot: Design, Implementation, and Field Trials - Jayawardena, Chandimal; Kuo; Broadbent, Elizabeth; MacDonald, Bruce A. (IEEE systems journal, 2016)
Socially assistive robotics is an important emerging research area. Socially assistive robotics is challenging as it is required to move robots out of laboratories and industrial settings to interact with ordinary human beings as peers, which requires social skills. The design process usually requires multidisciplinary research teams, which may comprise subject matter experts from various domains such as robotics, systems integration, medicine, psychology, gerontology, social and cognitive sciences, and neuroscience, among many others. Unlike most other robotic applications, socially assistive robotics faces some unique software and systems integration challenges. In this paper, the HealthBot robot architecture, which was designed to overcome these challenges, is presented. The presented architecture was implemented and used in several field trials. The details of the field trials are presented, and lessons learned are discussed with field trial results.